2012
DOI: 10.1002/hlca.201100360
|View full text |Cite
|
Sign up to set email alerts
|

A New Prenylated Isoflavone and a New Flavonol Glycoside from Flemingia philippinensis

Abstract: A new prenylated isoflavonoid, flemiphilippinin G (1), and a new flavonol glycoside, flemiphilippininside (2), along with eleven known isoflavonoids were obtained from the roots of Flemingia philippinensis (Merr. et Rolfe) Li. Their structures were elucidated on the basis of spectroscopic data. The in vitro cytotoxicities of compounds 1–13 against MCF‐7, A549, and Hep‐G2 cell lines were determined by using the MTT (=3‐(4,5‐dimethylthazol‐2‐yl)‐2,5‐diphenyl‐2H‐tetrazolium bromide) colorimetric assay, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Compound 8 showed a molecular ion peak at m/z 379.1169 [M+H] Table 1 1 H NMR (500 Hz) and 13 C NMR (125 Hz) spectroscopic data of compounds 1-5. a Additionally, the sharp proton signal at d H 8.24 (1H, s, H-2) indicated that 8 is based on a isoflavone skeleton with two substituents, a furan group and a 3-hydroxy-2,2-dimethyldihydropyran group (Fu et al, 2012). The HMBC cross-peaks from H-2 to C-9 (d C 149.8), and from H-1 000 to C-7 (d C 155.5), C-8 (d C 108.1) and C-9, suggested that the furan group was linked at the C-7 and C-8 positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 8 showed a molecular ion peak at m/z 379.1169 [M+H] Table 1 1 H NMR (500 Hz) and 13 C NMR (125 Hz) spectroscopic data of compounds 1-5. a Additionally, the sharp proton signal at d H 8.24 (1H, s, H-2) indicated that 8 is based on a isoflavone skeleton with two substituents, a furan group and a 3-hydroxy-2,2-dimethyldihydropyran group (Fu et al, 2012). The HMBC cross-peaks from H-2 to C-9 (d C 149.8), and from H-1 000 to C-7 (d C 155.5), C-8 (d C 108.1) and C-9, suggested that the furan group was linked at the C-7 and C-8 positions.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated column chromatography and preparative HPLC of the EtOAc soluble extract resulted in the isolation of ten new isoflavones, cudraisoflavones B-K (1-10), as well as 27 known isoflavones, 5,7,3 0 ,4 0 -tetrahydroxy-6,8-diprenylisoflavone (11), warangalone, auriculasin (Nkengfack et al, 1989), erythrinin B (12) (Jain and Sharma, 1974), gancaonin B (13), gancaonin A (Fukai et al, 1990), osajin, euchrenone b 8 , euchrenone b 9 (Mizuno et al, 1990), alpinumisoflavone, 4 0 -O-methyl-alpinumisoflavone (Olivares et al, 1982), 5,7,4 0 -trihydroxy-6,8- E (Sekine et al, 1999), anagyroidisoflavone A (Sato et al, 1995), euchrenone b 10 , senegalensin (Tanaka et al, 2001), eryvarin B (Tanaka et al, 2000), 5,7-dihydroxy-6-(2 00 -hydroxy-3 00 -methylbut-3 00 -enyl)-4 0 -methoxylisoflavone (Han et al, 2009), 3 0 ,5-dihydroxy-4 0 -methoxyl-2 00 ,2 00 -dimethylpyrano[6 00 ,5 00 -h]isoflavone, derrone (Tsukayama et al, 1992), 4 0 -O-methyl-2 00 -hydroxydihydroalpinumisoflavone (Abdel-Kader et al, 2006), isoerysenegalensein E (ElMasry et al, 2002), biochanin A (Klier et al, 2012), lupiwighteone (Tahara et al, 1991), 5,3 0 ,4 0 -trihydroxy-6 00 ,6 00 -dimethylpyrano-[2 00 ,3 00 ;7,6]isoflavone (Jain et al, 1978), erythrinin C (Tahara et al, 1985), and flemiphilippinin G (Fu et al, 2012), respectively (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1'), 154.6 (C-2'), 128.33 (C-3'), 137.9 (C-4'), 119.54 (C-5'), 124.8 (C-6'), 56.6 (OCH 3 , C-7'), 58.9 (OCH 3, C-4'), 56.01 (oxirane, C-2''), 56.51 (oxirane, C-3''), 64.0 (-CH 2 OH,C-3''). 228, 312nm in MeOH) exhibited the characteristic absorption maxima for a flavonoid 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Auriculasin ( 818 ) from the roots of Flemingia philippinensis exhibited an antiproliferative effect against PC-3 cells with a GI 50 value of 8.33 µ M. However, eriosematin, a chromone derivative, showed no activity (GI 50 > 100 µ M) which suggested B ring with 3′,4′-dihydroxy group in 818 would play an important role in inhibiting the growth of PC-3 cells (Kang et al 2016 ). Flemiphilippinin G ( 822 ) and 5,7,3′-trihydroxy-2′-(3-methylbut-2-enyl)-4′,5′-(3,3-dimethylpyrano) isoflavone ( 867 ) showed cytotoxicity against MCF-7, A549, and HepG2 cells with IC 50 values ranging from 4.8 to 24.8 µ M (Fu et al 2012 ). Tephrosin ( 893 ), cis -(6a β ,12a β )-hydroxyrotenone ( 894 ), and rotenone ( 895 ), isolated from Indigofera spicata , exhibited cytotoxicity against HT-29, 697 human acute lymphoblastic leukemia and Raji human Burkitt’s lymphoma cells with IC 50 values ranging from 0.1 to 9.0 µ M. Additionally, 894 (IC 50 0.1 µ M against HT-29 cells) and 895 (IC 50 0.1 µ M against HT-29 cells) did not show obvious toxic effects on normal CCD-112CoN cells, with IC 50 values over 100 µ M (Bueno Perez et al 2013 ).…”
Section: Biosynthesis Of Prenylated Flavonoidsmentioning
confidence: 99%